Diet at the onset of the Neolithic in northeastern Iberia: An isotope–plant microremain combined study from Cova Bonica (Vallirana, Catalonia) - Salazar-García, Domingo C.; Power, Robert C.; Daura, Joan; Sanz, Montserrat (Frontiers in Earth Science, 2022)
The emergence of Neolithic societies was transformative, impacting many aspects of life, particularly diet. The process of Neolithisation in Iberia is increasingly understood as the arrival of new people from the Central Mediterranean, who dispersed along the Iberian coasts introducing cereal production, herding and Cardial Pottery and associated material culture. Although research has clarified aspects of the cultigen-dominated economy of these new people, questions remain due to the limitations of conventional archaeobotanical and archaeozoological methods that tend to produce indirect evidence. The extent that these early farmers adopted Mesolithic staples, which are often difficult to detect with other methods, remains unclear. Furthermore, questions surround the nature of methods of food preparation Cardial Neolithic people used when incorporating grains in their diet. In this study, we examined direct evidence of diet from the Iberian Cardial Neolithic site of Cova Bonica (Vallirana, Baix Llobregat, Catalan Republic) using CN stable isotopes on bone and plant microremains trapped in dental calculus from six human individuals and associated fauna. Isotopes show a diet based on terrestrial C3 resources, with no evidence of aquatic or C4 resource consumption. Plant microremains (starches and phytoliths) provide evidence of cereal use, as well as of other plant foods. However, perhaps due to Bonica's early farmers choice of grain variety, their grain processing methods, or due to specific dental calculus formation factors, the grain assemblages are rather limited and provide scarce information on food preparation.